Biocontrol of Two Bacterial Inoculant Strains and Their Effects on the Rhizosphere Microbial Community of Field-Grown Wheat. (9th January 2021) - Wang, Xiaohui; Ji, Chao; Song, Xin; Liu, Zhaoyang; Liu, Yue; Li, Huying; Gao, Qixiong; Li, Chaohui; Zheng, Rui; Han, Xihong; Liu, Xunli
Abstract : Biocontrol by inoculation with beneficial microbes is a proven strategy for reducing the negative effect of soil-borne pathogens. We evaluated the effects of microbial inoculants BIO-1 and BIO-2 in reducing soil-borne wheat diseases and in influencing wheat rhizosphere microbial community composition in a plot test. The experimental design consisted of three treatments: (1) Fusarium graminearum F0609 (CK), (2) F. graminearum + BIO-1 (T1), and (3) F. graminearum F0609 + BIO-2 (T2). The results of the wheat disease investigation showed that the relative efficacies of BIO-1 and BIO-2 were up to 82.5% and 83.9%, respectively. Illumina MiSeq sequencing revealed that bacterial abundance and diversity were significantly higher (P < 0.05 ) in the treatment groups (T1 and T2) than in the control, with significantly decreased fungal diversity in the T2 group. Principal coordinates and hierarchical clustering analyses revealed that the bacterial and fungal communities were distinctly separated between the treatment and control groups. Bacterial community composition analysis demonstrated that beneficial microbes, such as Sphingomonas, Bacillus, Nocardioides, Rhizobium, Streptomyces, Pseudomonas, and Microbacterium, were more abundant in the treatment groups than in the control group. Fungal community composition analysis revealed that the relative abundance of the phytopathogenic fungi Fusarium and Gibberella decreased and that the well-known beneficial fungi Chaetomium, Penicillium, and Humicola were more abundant in the treatment groups than in the control group. Overall, these results confirm that beneficial microbes accumulate more easily in the wheat rhizosphere following application of BIO-1 and BIO-2 and that the relative abundance of phytopathogenic fungi decreased compared with that in the control group.